Novel Splice Variant in the HES7 Gene in Vietnamese Patient with Spondylocostal Dysostosis 4: A Case Report and Literature Review - Ha Minh Nguyen; Nguyen Thi Kim Lien; Thinh Huy Tran; Ngoc Lan Nguyen; Suong Bang Thi Nguyen; Thi Hong Chau Bui; Nguyen Van Tung; Le Tat Thanh; Nguyen Thi Xuan; Van Khanh Tran; Nguyen Huy Hoang (Diagnostics)
Spondylocostal dysostosis (SCDO) is a group of rare genetic disorders characterized by segmental vertebral defects and rib deformities due to congenital misalignment, fusion, or reduction in the number of ribs. The causes of the disease have been found in seven genes, including DLL3 (SCDO1, OMIM 602768), MESP2 (SCDO2, OMIM 608681), LFNG (SCDO3, OMIM 609813), HES7 (SCDO4, OMIM 608059), TBX6 (SCDO5, OMIM 602427), RIPPLY2 (SCDO6, OMIM 616566), and DLL1 (SCDO7). Among these, SCDO4, characterized by a short trunk, short neck, and mild nonprogressive scoliosis, is a rare form of reported cases. SCDO4 is identified as caused by homozygous or compound heterozygous variants in the HES7 gene (NM_001165967.2; NP_001159439.1). This study reports a novel homozygous HES7 splice variant (c.43-9T>A) detected in an SCDO4 patient by whole-exome sequencing and confirmed by Sanger sequencing. This variant was evaluated as an acceptor loss variant in intron 1 in the HES7 transcript by in silico analysis and was inherited from the patient’s parent. This study also reviews previous reports to provide a comprehensive overview of SCDO and help us to understand the pathogenesis to develop future treatment strategies.